2009
DOI: 10.1088/0004-637x/696/1/l84
|View full text |Cite
|
Sign up to set email alerts
|

Primordial Circumstellar Disks in Binary Systems: Evidence for Reduced Lifetimes

Abstract: We combine the results from several multiplicity surveys of pre-main-sequence stars located in four nearby star-forming regions with Spitzer data from three different Legacy Projects. This allows us to construct a sample of 349 targets, including 125 binaries, which we use to to investigate the effect of companions on the evolution of circumstellar disks. We find that the distribution of projected separations of systems with Spitzer excesses is significantly different (P ∼ 2.4e-5, according to the KS test for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
194
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(208 citation statements)
references
References 39 publications
13
194
1
Order By: Relevance
“…Cieza et al (2009), like Ratzka et al (2005, found no evidence for multiplicity. C10 identified the system as a TD and determined it to be a K7-type star, in agreement with our measurements above.…”
Section: Comparison To the Literaturementioning
confidence: 77%
See 1 more Smart Citation
“…Cieza et al (2009), like Ratzka et al (2005, found no evidence for multiplicity. C10 identified the system as a TD and determined it to be a K7-type star, in agreement with our measurements above.…”
Section: Comparison To the Literaturementioning
confidence: 77%
“…However, several studies (Ghez et al 1997;White & Ghez 2001;Cieza et al 2009;Duchêne 2010;Kraus et al 2012) have found protoplanetary disk fractions are lower for young ( 5 Myr) binary systems with a<50 au than for single stars or wider binaries. With the exception of Kraus et al (2012), these studies were not sensitive to the tight binary systems to which our study was especially sensitive.…”
Section: Sample Sensitivity To Companionsmentioning
confidence: 99%
“…Binaries with separations closer than ∼40 AU show a lower frequency of infrared excess compared with single or wide binary sources (e.g., Monin et al 2007;Cieza et al 2009;Kraus et al 2012). This suggests that these triples and quadruples should have a higher fraction of mixed pairs.…”
Section: Mixed Systemsmentioning
confidence: 99%
“…Because the close components should exhibit rapid disk clearing (Monin et 4 al. 2007;Cieza et al 2009;Kraus et al 2012), whether this parameter affects our discussion or not is explored in later sections. Binarity in these systems, especially those that are widely separated, has yet to be confirmed by multi-epoch astrometry; therefore, many of these systems are candidates of binaries.…”
Section: Sample and Archival Datamentioning
confidence: 99%
See 1 more Smart Citation